Neurological Disorders Associated With COVID-19 Hospital Admissions: Experience of a Single Tertiary Healthcare Center - Dhillon, Permesh Singh; Dineen, Robert A.; Morris, Haley; Tanasescu, Radu; Nikfekr, Esmaeil; Evans, Jonathan; Constantinescu, Cris S.; Hosseini, Akram A. (Frontiers in Neurology, 2021)
Background: Early reports have detailed a range of neurological symptoms in patients with the SARS-CoV-2 infection. However, there is a lack of detailed description and incidence of the neurological disorders amongst hospitalized COVID-19 patients. We describe a range of neurological disorders (other than non-specific neurological symptoms), including their clinical, radiological, and laboratory findings, encountered in our cohort of COVID-19 patients admitted to a large tertiary institution. Methods: We reviewed our prospectively collated database of all adult Neurology referrals, Neurology and Stroke admissions and Neurological multi-disciplinary team meetings for all hospitalized patients with suspected or proven COVID-19 from 17 March 2020 to 31 August 2020. Results: Twenty-nine of 1,243 COVID-19 inpatients (2.3%) presented with COVID-19-related neurological disorders. The mean age was 68.9 ± 13.5(SD) years, age range of 34–97 years, and there were 16 males. Twenty two patients had confirmed, five were probable and two had suspected COVID-19 infection according to the WHO case classification. Eight patients (27%) required critical care admission. Neurological symptoms at presentation included acute confusion and delirium, seizures, and new focal neurological deficits. Based on the pre-defined neurological phenotype, COVID-19 patients were grouped into four main categories. Sixteen patients had cerebrovascular events (13 with acute ischemic stroke and three had hemorrhagic features), seven patients were found to have inflammatory, non-inflammatory and autoimmune encephalopathy (including two with known Multiple Sclerosis), whilst disorders of movement and peripheral nervous system were diagnosed in three patients each. Conclusion: Although the exact prevalence and etiology remain unclear, new onset of neurological disorders, in addition to anosmia, is non-sporadic during the acute COVID-19-infection. Longitudinal follow-up of these patients is required to determine the clinical and functional outcome, treatment response and long-term effects of the SARS-CoV-2 infection.